Higher dermal exposure of cashiers to BPA and its association with DNA oxidative damage. (January 2017) - Lv, Yanshan; Lu, Shaoyou; Dai, Yanyan; Rui, Caiyan; Wang, Yongjun; Zhou, Yuanxiu; Li, Yanru; Pang, Qihua; Fan, Ruifang
Abstract: Bisphenol A (BPA) is a widely used chemical in the production of many polycarbonate plastics, epoxy resin linings for food and beverage containers and thermal papers. Oral intakes from the contaminated diets were considered as the predominant source of BPA exposure for humans. However, due to the high levels of BPA on thermal receipts and their wide applications in our daily life, the amount of BPA be transferred to the skin after holding thermal paper should not be underestimated, particularly for cashiers. To investigate the contribution of BPA exposure levels via the dermal contact route and the relationship between BPA exposure level and oxidative DNA damage, six male volunteers were recruited and required to simulate the cashiers' work and handle the thermal receipts during the study period. Triclosan (TCS, an antimicrobial compound used widely in personal health and skin care products) was applied as a reference compound. Their urinary BPA, TCS and 8-hydroxy-2′-deoxyguanosine (8-OHdG) concentrations were determined by high performance liquid chromatography/ tandem spectrometer (LC/MS/MS). The results showed that after handling the thermal receipts, the urinary BPA concentrations of volunteers increased 3 times of those before the experimental period. But TCS levels in urine kept stable. There existed a correlation between BPA exposure and 8-OHdG (R 2 = 0.237, p < 0.001), but not between TCS and 8-OHdG concentrations (R 2 = 0.026, p < 0.777), indicating that more BPA exposure could lead to higher oxidative DNA damage. That the increases in 8-OHdG levels in urine being almost consistent with those of BPA suggested that handling thermal receipts resulted in the increasing BPA intakes and BPA exposure was correlated with DNA oxidative damage. After 48 h of the end of handling thermal receipts, the urinary BPA levels did not descend to the levels before experiment, suggesting that the excretion of BPA via dermal contact was over 48 h. BPA exposure through dermal contact route contributed 51.9% to 84% to urinary BPA levels with the GM ratio of 70.9% for cashiers, indicating that it might be seriously underestimated for cashiers according to the previous studies. More attentions should be paid on the exposure of BPA via dermal penetration for cashiers. Graphical abstract: Highlight: BPA exposure via dermal absorption is seriously underestimated for cashiers. The contribution ratios of BPA intakes via dermal absorption range from 51.9% to 84.8% for cashiers. The intake and metabolic time of dermal absorption of BPA is lagged over 48 h. Higher exposure to BPA could lead to higher oxidative DNA damage.